Assessment of Lithuanian Energy Sector Influence on GDP - Irena Mačerinskienė; Inna Kremer – Matyškevič (Montenegrin Journal of Economics, 2017)
The relationship between the Economic growth and Energy Sector performance is unquestionable. Honewer it is not an easy task to evaluate the strength of this relationship. The majority of scientists are investigating the impact of certain Energy Sector’s activities on the overall energy consumption, climate change or Economic growth. This article analyzes the influence of Energy Sector to GDP of Lithuania. The objective of the research is to show how the results of Lithuanian Energy Sector in 2005 – 2015 have been changed and to determine their impact on GDP. The concept of Energy Sector is presented first. Secondly, a methodology for analyzing the performance of the Economic growth and Energy Sector is described. Thirdly, the analysis of the activities of Energy Sector and its influence on GDP has been analyzed. The proposed model of the impact of the Energy Sector's activities on the growth of GDP in the article combines six main aspects of the research: participants in the Energy Sector; Energy balance indicators; Changes in energy product prices; The value added created by the Energy Sector; The main taxes paid by Energy Sector as part of the National budget revenue; The net profitability of the Energy Sector. This model is applicable for analyzing the aggregate performance indicators of Energy Sector and its impact on the growth of GDP. Hypothesis of this research - Lithuanian energy sector has a statistically significant influence on GDP. The findings showed that GDP and Energy Sector indicators, after a year of crisis, tended to grow. But the impact of these indicators on GDP is weak. However, particularly high correlation ratios between them may indirectly affect the change in GDP.